The dynamics of foreign exchange derivative use in China - Yidi Sun; Bruce Morley (Journal of Risk and Financial Management, 2021)
The aim of this study is to determine the main factors affecting the use of foreign exchange hedging instruments by Chinese firms, following their regulatory changes in the derivative markets. The original contributions to this literature include the use of a panel dataset of 316 Chinese firms with the data running from 2012 to 2017 and a dynamic random effects probability approach. The results suggest the main determinants of derivative use are the overseas trade conducted by these firms, with some evidence of non-linearity, as well as firms being more likely to use derivatives when there is more information asymmetry and agency problems, potentially due to greater controls on their use in China.
Keywords: 330; derivative; dynamic panel; exports; hedging